The Investigation of the Antioxidative Properties of the Synthetic Organoselenium Compounds in Liver Tissue of Rat with Histological and Biochemical Analyses - Zeliha Selamoglu; Ismet Yilmaz (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Oxidative stress is described as the formation of toxic effect due to the deficiency of cellular antioxidative level toward the level of reactive oxygen species (ROS). The excess production of ROS or the decrease in the antioxidative defense system could be the cause for oxidative stress. 7,12-dimethylbenz[a]anthracene (DMBA) that is known to be the major cause the increment in lipid peroxidation level and the oxidative damage in the rat liver. As a fundamental trace elements, selenium as a part of anti-oxidative defense system is responsible for the immune system as part of enzymes in defense system. Methods: Organoselenium compounds [1-isopropyl-3- methylbenzimidazole-2-selenone (Se I ) and 1, 3-di-pmethoxybenzylpyrimidine- 2-selenone (Se II)] that were prepared in the laboratories. The effects of synthetic organoselenium compounds (Se I and Se II) against DMBA-induced changes in levels of some [catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), and glutathione reductase (GR) activities and total glutathione (GSH), malonedialdehyde (MDA)] parameters in rat liver were investigated. Histopathological changes in the liver tissues of rats were examined by light microscopy. Results: Because the selenium has an anti-oxidative properties toward the damaged induced cells, organoselenium compounds prepared in our laboratories, Se I and Se II, have tested for chemically induced rat liver tissues. The results showed that endogen antioxidant enzymatic activities changes and the preventing of oxidative damage in lipid peroxidation are important findings in vivo of this research. Conclusion: Various changes were observed in liver tissue of rats in the all experimental groups.